Successful Pregnancy in a Couple with Severe Male Factor Infertility after Selection of Sperm with Cytoplasmic Droplets - Jenna Bellish; David H. McCulloh; Khaliq Ahmad; Peter G. McGovern (Case Reports in Obstetrics and Gynecology)
We present live births resulting from two separate IVF cycles in a couple in which ICSI was performed with sperm specifically selected for presence of small cytoplasmic droplets. These cycles followed previous cycles using standard sperm selection methods in which very poor embryo development and no pregnancies ensued. The male partner was diagnosed with severe male factor infertility including elevated DNA fragmentation.